The influence of financial constraints and firm age on firm performance: The mediating effect of digital transformation - Angelina, Cecilia; Putri, Ni Putu Andhini Pranadia; Rusmanto, Toto (Edelweiss Applied Science and Technology, 2025)
Amid the increasing challenges of digital transformation, Indonesia's non-cyclical consumer sector faces difficulties in terms of innovation and competitiveness. This sector covers primary consumer needs that are resilient to economic crises but faces high demands for innovation and competition. This study explores the effect of financial constraints and firm age on firm performance, with digital transformation as a mediating variable. Based on empirical evidence from 210 companies from 2019-2023 analyzed using quantitative methodology with MAXQDA and STATA, the results show that financial constraints significantly negatively impact firm performance, reflecting the difficulty of obtaining funding for strategic investments, including digital transformation. Although expected to mediate the relationship, digital transformation did not show a statistically significant effect. Firm age provides stability through experience but faces challenges in adapting to technological changes and dynamic markets. The practical implication is that companies must allocate funds more efficiently for digitalization. Investors should consider digitalization readiness and evaluate the firm’s financial constraints before investing because limited funds can hinder innovation and growth. The government also needs to encourage access to digital funding to accelerate the transformation of this sector.